WATER QUALITY MODELLING AND POLLUTANT LOAD CARRYING CAPACITY ANALYSIS OF AKELAMO RIVER, NORTH MALUKU - Geta A P, Kristoforus
Rivers are body of water that affect many environmental components and ecosystems. The quality of river water also affects the capacity of the pollutant load released by the mine. River quality is strongly influenced by watershed land use. The Akelamo River has contributions from a catchment area that contains various mining activities and various uses of forest areas. Water from nickel mining activities is characterized by low pH and high TSS, as well as the presence of dissolved iron (Fe) and dissolved nickel (Ni). The Akelamo River is located in a tropical region with high rainfall. This causes the potential for runoff water from mining activities that must be managed to have a large volume. The Akelamo pollution index calculation is 0.421. When referring to the second class quality standard of Government Regulation No. 22 of 2021 concerning the Implementation of Environmental Protection and Management, the Akelamo River is categorized as a river with good or unpolluted status. The Akelamo River area covered in this study is 9.2 km from upstream to downstream. The objective is to conduct river segmentation, spatial analysis, modeling, and analyze the capability of the river to receive pollutant loads. From the analysis, the amount of pollutant load that can be discharged into the Akelamo River without causing the river to become polluted and determine the environmental management of the watershed that can be carried out. Simulations were conducted using QUAL2Kw software to simulate pH and TSS parameters with various scenarios. Fe and Ni parameters were simulated using mass balance calculations. For the results of the calculation of pollutant load capacity, Akelamo River has a pollutant load capacity value for TSS, Fe, and Ni parameters of 54300.97 kg/day, 192 kg/day, and 30.87 kg/day, respectively.